Analisis Penerapan Manajemen Risiko Untuk Menjaga Kepercayaan Pelanggan Pada Usaha Tour & Travel - Listi Sinta Nur Oktaviani; Fidelairna Daniswara; Dena Destiani; Najla Putri Pramesdianti; Alfiana (Indo Publishing, 2025)
Customer trust is an important component of any successful business relationship, as it forms the basis for long-term customer loyalty and satisfaction. Customer trust is the confidence and belief that customers have in an organization or brand, which includes the expectation that the organization will fulfill its promises and provide the services or products that customers expect. This study analyzes the application of risk management based on the ISO 31000:2018 standard to maintain service quality. The methods used are interviews and observations of tour and travel businesses. The results of the study show that risk identification, analysis, and control, such as reservation errors, service delays, and customer complaints, can increase trust and business continuity.